Mastering Java 2 - Zukowski, John (Sybex, 1998)
Part 1 includes history, language and programming concepts of Java. Part II examines the packages in Java-speak, including basic animation, transferring information between applications, and making programs Internet savvy. Part III deals with security concepts and integration of Java with CORBA.